2015
DOI: 10.1186/s40557-014-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of work-related upper extremity musculoskeletal disorders in male cameramen

Abstract: ObjectiveThe aim of this study is to determine the risk factors related to upper extremities work-related musculoskeletal disorders (WRMSDs) in cameramen.MethodsA questionnaire survey was performed on 166 cameramen in a broadcasting station. The questionnaire consisted of questions on the general characteristics, the health behavior, work type and duration, physical burden, ergonomic posture, and musculoskeletal symptoms. Definition of musculoskeletal disorders was based on NIOSH criteria.ResultsThe positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…There was a total of 37,845 participants in 18 studies reporting on physically active workers. The prevalence estimates or odds ratios in those over 50 increased in 14 of these 18 studies [ 13 , 14 , 21 , 23 , 25 , 29 – 31 , 34 – 39 ], remained stable in two [ 22 , 28 ] and decreased in one [ 24 ]. One study of farmers reported data only for two age groups, using 65 as a cut point and found that shoulder pain reporting decreased in the older group [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was a total of 37,845 participants in 18 studies reporting on physically active workers. The prevalence estimates or odds ratios in those over 50 increased in 14 of these 18 studies [ 13 , 14 , 21 , 23 , 25 , 29 – 31 , 34 – 39 ], remained stable in two [ 22 , 28 ] and decreased in one [ 24 ]. One study of farmers reported data only for two age groups, using 65 as a cut point and found that shoulder pain reporting decreased in the older group [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have measured the level of physiological stress experienced by cameramen in terms of heart rate and oxygen consumption and classified cameramen’s tasks as physiologically heavy work [ 15 ], analyzed occupational suprascapular nerve entrapment among cameramen [ 22 ], and identified ergonomic factors and physical burden as risk factors of WRMDs in cameramen, which were found to affect the shoulders most commonly [ 14 ]. However, these studies limited their research subjects to cameramen only.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, workplace factors (e.g., time pressure, poor work/rest schedule, and low job control), physical factors (e.g., old age and elevated body mass index), and psychosocial stress have also been reported as risk factors of WRMDs [ 13 ]. A study has reported that these ergonomic risk factors are present in workplaces for cameramen and that they affect the incidence of WRMDs among cameramen [ 14 ]. Another study has reported that because cameramen perform physically demanding tasks and thus experience high levels of physiological stress, their occupation must be classified as heavy work [ 15 ].The environment for making TV programs in Korea lacks production costs and staff, giving cameramen long working hours and short break times.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, fewer studies reported the relationship between BMI and EMG signal variations. Indeed, BMI was associated with increased prevalence of work-related musculoskeletal disorders (WMSDs) and increased scores of musculoskeletal discomfort [40,41]. It may be necessary to investigate the longer term effects of BMI on muscle activation in future work since BMI influences chronic musculoskeletal pain/discomfort in a roundabout way [42].…”
Section: Discussionmentioning
confidence: 99%